Love by design - McGovern, Kieran (Đồng Nai, 2009)
Somehow her own fictional brooding hero had turned up in person right under her own roof, and now all romance writer Jackie MacNamara had to do was convince stubborn Nathan Powell that happily-ever-after began at home—and in her arms.… She was the sexiest thing in a hard hat that architect Cody Johnson had ever seen, but structural engineer Abra Wilson also had a will as strong as a steel girder—and just about as flexible. But Cody had plans for Abra that not even this spirited beauty could resist.…